Monomyth, Mirrors, and Maddening Mothers—Otherized Female Identity in Coraline - Jaime Segura San Miguel (HyperCultura)
Abstract: This article, which unites narratology, comparative mythology, and psychoanalysis, examines the ways in which mother-daughter relationships in a parallel world affect female identity in Henry Selick’s Coraline, and how this process of individuation is replaced by the mythical heroine’s journey. One of the cornerstones of object relations theory posits that the mother is the first object we ever internalize, and that this deeply affects the way in which we construct our reality and identity. Particularly, attachment becomes a necessary foundation for undergoing the individuation process and the creation of the self. Coraline presents a strong heroine living in a neglected and isolated reality. By using the mythographic feminist version of the monomyth—Maureen Murdock’s Heroine’s Journey—along with psychoanalytical object relations theory, a model is used to analyze and explain how identity is perceived and constructed in Coraline. To attain this new identity, Coraline will need to change the relationship with her mothers through “mirror/unmirror” phases and go deeper into the parallel mythical world where she can become her ideal self. Finally, this article ends with an explanation of Coraline’s inner fight to define herself in both worlds and how this eventually leads to a less otherized self.